ANALISIS PERANAN BADAN LEGISLASI DEWAN PERWAKILAN RAKYAT REPUBLIK INDONESIA DALAM PENYUSUNAN UNDANG-UNDANG - Putra, Dwiky Ramanda; Riwanto, Agus (Res Publica: Jurnal Hukum Kebijakan Publik, 2018)
This study aims to determine the implementation of the roles and responsibilities of the Legislative Body of the House of Representatives in the drafting of the Law in the House of Representatives in order to create good legislation and see the system of drafting the Law for the creation of legislative products produced by the legislature can form legislation good legislation to implement in Indonesia, The problem of the legal system in Indonesia which resulted in the legislative body as one of the parliamentary fittings of the Republic of Indonesia is not optimal in answering the legal needs of the community.This research uses descriptive normative research method. Approach This study uses a historical approach to answer the first formula and conceptual approach to answer the formulation of the second problem. The types and legal materials used in this study include primary and secondary legal materials. Techniques of collecting legal materials through document studies. The analytical technique used is the technique of legal material analysis with deductive logic.Based on the results of research That the role of the legislative body in the preparation of the Act is still not optimal in running tupoksi from the legislation because many of the various interests that led to the deliberation of the Draft Law will affect the performance of the Legislative function of the House,